Educational Sciences in Morocco: Foundations, Advances, Challenges, and Future Prospects - MAZOUAK ABDERRAZZAK; MOUMEN, Aziz (International Journal of Scientific Research and Innovative Studies, 2024)
Educational sciences, referred to in Arabic as "Uloom al-Tarbia" (علوم التربية), represent a multidisciplinary field dedicated to studying teaching methods, learning psychology, educational policy, and school administration. Morocco's educational landscape has undergone significant reforms, emphasizing the role of educational sciences in meeting the needs of an evolving society. This article explores the foundations, developments, ongoing challenges, and future potential of educational sciences within Morocco’s educational system. By addressing these issues, Morocco aims to enhance teaching practices, inform policy-making, and create an inclusive educational environment that supports academic and personal development for all students. Keywords: Educational sciences, Morocco, pedagogy, curriculum design, educational psychology, educational policy, school administration, teacher training, professional development, inclusivity, educational equity, academic standards, socio-cultural context, learning environments. Received Date: April 20, 2024 Accepted Date: May 20, 2024 Published Date: June 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/210